A közigazgatási térfelosztás változásai Magyarországon - Hajdú, Zoltán (Tér és Társadalom, 1996)
While giving a brief introduction and analysis of the spatial history of Hungarian public administration, the author focuses on the following tendencies: in the historical-spatial development of the Hungarian public administration, continuity and interruption were present simultaneously, to a large extent in connection with the turning points of the history of the state. The most particular and most important regional unit of the Hungarian public administration was the county that itself changed several times with respect to both its function and spatial appearance. With the "foreign ownership" of the central power after 1526, the county developed into a special national-political institution and became the stage of national opposition. The historical county and county system reached the top of their power by the mid-19th century: Participant of law making, the regional representative of jurisdiction, general authority of public administration, the most important regional organ of the executive power. The civil transformation weakened the feudal type power unit of the counties, with the separation of the branches of power, the former importance of the county governments declined, the state administration pushed county governments out of more and more significant fields. – In the period of the civil transformation, a significant correction of the regional division of the counties took place, but carefully considering the historically formed county borders. The changes of the state border following World War I basically rearranged the regional order of inner public administration. The territorial and population imbalances among the counties were stronger than ever. Between the two world wars the nationalisation process of the public administration accelerated. Before and during World War II the administrative space of the counties pulsed according to the changes of the state border. The state socialist system, built between 1945 and 1950, carried out fundamental changes in the functions and operation of public administration, at the same time it only applied corrections in the regional structure. In the second half of the state socialist era some elements of self governments gradually appeared again in the Hungarian public administration, in a sense public administration approached the historical traditions of Hungary. The systemic change of self government public administration in 1990 brought a functional reform but not a real regional one. The reform of 1990 appreciated the role of the self governments of the settlements for the first time in the history of the Hungarian public administration, and it partly led to the fact that the regional governments were depreciated as never before in the administrative history of Hungary. The county governments had never been as weak and deprived of functions in the history of the Hungarian public administration as after 1990. The Hungarian public administration and regional system is facing new challenges and bad needs for reforms.